The cost of prevalent and incident cardiovascular disease in people with type 2 diabetes in Scotland: data from the Scottish Care Information–Diabetes Collaboration. Issue 11 (14th February 2020) - McMeekin, P.; Geue, C.; Mocevic, E.; Hoxer, C. S.; Ochs, A.; McGurnaghan, S.; Colhoun, H. M.; Wild, S. H.; Wu, O.; ,
Abstract: Aim: To compare costs for three groups of people with type 2 diabetes, those at high risk of future cardiovascular disease, those without cardiovascular disease and those with established cardiovascular disease, and to also compare costs incurred by people with type 2 diabetes with an incident cardiovascular disease event with those who remain incident event‐free over a 3‐year period. Methods: Data about people with type 2 diabetes in Scotland were obtained from the Scottish Care Information Diabetes registry. Data linkage was used to retrieve information on healthcare utilization, care home use and deaths. Productivity effects were estimated for those of non‐pensionable age. We estimated costs over 12 months (prevalent cardiovascular disease) and 3 years from incident cardiovascular disease event. Results: Mean annual cost per person with established cardiovascular disease was £6900, £3300 for a person at high risk of future cardiovascular disease, and £2500 for a person without cardiovascular disease and not at high risk. In year 1, the cost of an incident cardiovascular disease event was £16 700 compared with £2100 for people without an incident event. Over 2 years, the cumulative costs were £21 500 and £4200, and by year 3, £25 000 and £5900, respectively. Conclusions: Cardiovascular disease in people with type 2 diabetes places a significant financial burden on healthcare and the wider economy. Our results emphasize the financial consequences of cardiovascular disease prevention strategies. What's new?: People with type 2 diabetes are at an elevated risk of being affected by cardiovascular disease. Cardiovascular disease is the leading cause of co‐morbidity and death among people with type 2 diabetes. Cost comparisons are usually between two groups of people with type 2 diabetes, those with and without cardiovascular disease. The majority of studies take a cardiovascular disease prevalence‐based approach to estimating the cost of illness.